MARISA DE FILIPPI, Materiali per un corso di esegesi delle fonti del diritto romano, Cacucci Editore, Bari 2008, ss. 111 - Jońca, Maciej (Zeszyty Prawnicze, 2017)
MARISA DE FILIPPI, Materiali per un corso di esegesi delle fonti del diritto romano, Cacucci Editore, Bari 2008, ss. 111